1990
DOI: 10.1111/j.1526-4610.1990.hed3004201.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Evaluation of Common and Classic Migraine. Part I. Ultrasonic Features During the Headache‐Free Period

Abstract: To study vascular abnormalities in migraine, transcranial Doppler (TCD) was used for evaluation of 100 consecutive patients with either common or classic migraine during the headache-free period. We insonated the basal cerebral arteries and the internal carotid artery (ICA) in the neck. Particular ultrasonic features in migraineurs included intracranial elevations of mean flow velocity (MFV) above 3 standard deviations of normal values in 16%, probably reflecting increased vasotonus. Marked asymmetry of MFV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 3 publications
7
60
1
Order By: Relevance
“…Alternatively, it has been suggested that vascular changes and ocular sym pathetic dysfunction may result from the activation of trigeminovascular reflexes or the antidromic release of va soactive substances from trigeminal nerve terminals [23. 24], Whatever the reason, cerebral blood asymmetries have been reported as more frequent in headache-free migraineurs than in normals using the l33Xe inhalation technique [5], and asymmetries of MFV greater than 20cm/s in corresponding intracranial arteries have been detected on TCD in 12 of 100 consecutive headache-free migraineurs [25], These findings are in agreement with the idea, pro posed by Friberg ct al. [16] that in migraineurs the insta bility of cerebrovascular tone is the prime pathological condition affecting blood vessels.…”
Section: Discussionsupporting
confidence: 81%
“…Alternatively, it has been suggested that vascular changes and ocular sym pathetic dysfunction may result from the activation of trigeminovascular reflexes or the antidromic release of va soactive substances from trigeminal nerve terminals [23. 24], Whatever the reason, cerebral blood asymmetries have been reported as more frequent in headache-free migraineurs than in normals using the l33Xe inhalation technique [5], and asymmetries of MFV greater than 20cm/s in corresponding intracranial arteries have been detected on TCD in 12 of 100 consecutive headache-free migraineurs [25], These findings are in agreement with the idea, pro posed by Friberg ct al. [16] that in migraineurs the insta bility of cerebrovascular tone is the prime pathological condition affecting blood vessels.…”
Section: Discussionsupporting
confidence: 81%
“…They reported that all intracranial arteries in the migraine patients had higher average flow rates, and that the vascular reactivity in the PCAs in response to eye closing was significantly higher in the migraine group than in the control group (26 Kastrup et al studied 20 migraine patients and 30 controls using TCD of both MCAs and PCAs, and reported that mean cerebrovascular blood flow velocity and CO2 reactivity were higher in the patients with migraine (15). The same year Kastrup et al investigated metoprolol treatment and reported that it had no effect on reactivity in migraine patients that had elevated reactivity before treatment (16).…”
Section: Discussionmentioning
confidence: 99%
“…6 -8 Recently, transcranial Doppler ultrasonography (TCD), a noninvasive technique used to assess the dynamics of the intracranial circulation in various physiological and pathological conditions, 9 has been used to study migraine. The CO 2 reactivity of the cerebral arteries 10 and the blood flow velocity during the migraine-free phase 11 have been measured and the flow velocity values estimated during both attack and headache-free periods. 12 The present study compares blood flow velocities using TCD in the headache-free period and within the first 6 hours of the attack in cases of migraine with and without aura.…”
mentioning
confidence: 99%